Identification of antibiotic resistant bacteria community and a GeoChip based study of resistome in urban watersheds. (1st December 2016) - Low, Adrian; Ng, Charmaine; He, Jianzhong
Abstract: Urban watersheds from point sources are potential reservoirs of antibiotic resistance genes (ARGs). However, few studies have investigated urban watersheds of non-point sources. To understand the type of ARGs and bacteria that might carry such genes, we investigated two non-point source urban watersheds with different land-use profiles. Antibiotic resistance levels of two watersheds (R1, R3) were examined using heterotrophic plate counts (HPC) as a culturing method to obtain counts of bacteria resistant to seven antibiotics belonging to different classes (erythromycin, kanamycin, lincomycin, norfloxacin, sulfanilamide, tetracycline and trimethoprim). From the HPC study, 239 antibiotic resistant bacteria were characterized for resistance to more antibiotics. Furthermore, ARGs and antimicrobial biosynthesis genes were identified using GeoChip version 5.0 to elucidate the resistomes of surface waters in watersheds R1 and R3. The HPC study showed that water samples from R1 had significantly higher counts of bacteria resistant to erythromycin, kanamycin, norfloxacin, sulfanilamide, tetracycline and trimethoprim than those from R3 (Analysis of Similarity (ANOSIM), R = 0.557, p < 0.01). Of the seven antibiotics tested, lincomycin and trimethoprim resistant bacteria are greater in abundances. The 239 antibiotic resistant isolates represent a subset of resistant bacterial populations, including bacteria not previously known for resistance. Majority of the isolates had resistance to ampicillin, vancomycin, lincomycin and trimethoprim. GeoChip revealed similar ARGs in both watersheds, but with significantly higher intensities for tetX and β-lactamase B genes in R1 than R3. The genes with the highest average normalized intensities in R1 and R3 were tetracycline (tet) and fosfomycin ( fosA) resistance genes, respectively. The higher abundance of tetX genes in R1 is congruent with the higher abundance of tetracycline resistant HPC observed in R1 samples. Strong correlations ( r ≥ 0.8) of efflux pumps with antimicrobial biosynthesis genes suggest that natural production of antimicrobials may act as a selective pressure of transporter proteins in the absence of antibiotics from anthropogenic sources. In conclusion, distinct antibiotic resistant bacteria phylotypes and a variety of ARGs were present in the non-point sources urban watersheds of different land-use profiles, suggesting that ARG risk assessments and monitoring studies need to include these types of watersheds. Graphical abstract: Highlights: Lincomycin and Trimethoprim resistance are common amongst environmental bacteria. Two bacterial isolates were resistant to all 11 antibiotics tested. GeoChip identified 18 groups of antibiotic resistance genes in watersheds. TetX and β-lactamase B genes were found to be more abundant in watersheds. Strong correlations ( r ≥ 0.8) of efflux pumps to antimicrobial biosynthesis genes.